REVIEW: PROCESS OF FLUID BED GRANULATOR PARAMETERS AT THE TIME OF SCALE UP IN GRANUL PRODUCTION - Diki Zaelani; Yoga Windhu Wardhana; Anis Yohana Chaerunisaa (Medical Sains : Jurnal Ilmiah Kefarmasian, 2023)
Scaling up is one of the difficulties faced by the production process of the pharmaceutical industry. We must manufacture in higher quantities than a laboratory size with set requirements as we scale up. Understanding the crucial variables that affect the final product's specifications will aid in choosing appropriate upgrade settings. Fluidized-bed granulation is one of the most frequently used techniques to increase the scale of the pharmaceutical industry. The complex fluidized bed granulation process is influenced by several factors. The most important process variables were the intake air temperature and humidity, concentration of the binder solution, spray rate, atomizing air pressure, and air flow rate. Numerous investigations have examined the effects of large-scale fluid bed granulation. An improved fluid bed granulation technology was employed based on the relative droplet size and moisture content of the powder in the bed after the spraying cycle. These values are comparable, demonstrating that the granulation procedure can be enhanced by considering only the moisture content of the powder and relative droplet size. Keywords: fluid bed granulation, process parameters, scale up